Ответ:98÷2=49;38÷2=19;58÷2=29;78:2=39
Наверное вот так .
3 8/9-х=1 5/8
х=1 5/8-3 8/9
х=-2 19/72
(1 5/8-3 8/9= 1 45/72-3 64/72=-(3 64/72-1 45/72)=-2 19/72)
X² + y² = 1
y = kx + 1
Подставим второе в первое
x² + (kx + 1)² = 1
x² + k²x² + 2kx + 1 = 1
x² + k²x² + 2kx = 0
разложим на множители
x*(x + k²x +2k) = 0
Первое решение
x₁ = 0
y₁ = kx₁ + 1 = 1
(0;1)
Второе решение
x₂ + k²x₂ +2k = 0
x₂(1+k²) = -2k
x₂ = -2k/(1+k²)
y₂ = kx₂ + 1 = -2k₂/(1+k²) + 1 = (1-k²)/(1+k²)
(-2k/(1+k²); (1-k²)/(1+k²))
левую часть домножаешь на x+4, правую - на 4x-1
1.5(x+4)=0.4(4x-1)
1.5x+6=1.6x-0.4;
1.5x-1.6x+6+0.4=0;
6.4-0.1x=0;
x=64;